INCREASED STUDENT MOTIVATION AND LEARNING OUTCOMES THROUGH STAD TYPE COOPERATIVE LEARNING MODEL ON THE MATERIAL OF BODY PARTS IN PLANTS - Khalilatul Aziz; Isna Nurul Inayati (INCARE, International Journal of Educational Resources, 2023)
This research was motivated by the low learning outcomes of students in class IV science subjects MI Al-Ishlah Sumberkombang Kalipare. Many factors that researchers encounter in the learning process that affect learning outcomes such as: 1) less variety of methods used by teachers. 2) Students lack passion for learning. So to overcome this problem, researchers apply the STAD Type Cooperative learning model so that student learning outcomes increase. The type of research used is Classroom Action Research (PTK) with a quantitative approach. The PTK model used is the Kemmis and Mc Taggart model, researchers carry out research through two cycles, namely cycles I and II. With the following steps: 1) Planning, 2) Implementation 3) Observation, 4) Reflection. In data collection, researchers use the necessary research instruments including, interviews, written tests, questionnaires, observation sheets, and documentation. The results of this study show that: 1) Increasing Student Motivation and Learning Outcomes through the STAD Type Cooperative Learning Model on Plant Body Part Material is carried out by grouping students into 3 heterogeneous groups, namely academic abilities, gender, race, or different ethnicities. 2) The STAD type cooperative learning model can increase motivation and learning outcomes of plant body parts material in class IV science subjects MI Al-Ishlah Sumberkombang Kalipare, this can be seen from the motivation of cycle I students all students reach a medium level of motivation, and cycle II there are 6 students who reach a high level of motivation and 4 students reach a medium level of motivation. As well as the learning outcomes of cycle I there are 5 students or 50%, and cycle II there are 8 students or 80% whose scores are above KKM.